2021
DOI: 10.1111/asj.13503
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure of the bovine rumen as affected by feeding cashew nut shell liquid, a methane‐inhibiting and propionate‐enhancing agent

Abstract: The effect of cashew nut shell liquid (CNSL) feeding on bacterial and archaeal community of the bovine rumen was investigated by analyzing clone libraries targeting 16S rRNA genes, methyl‐coenzyme reductase A‐encoding genes (mcrA), and their respective transcripts. Rumen samples were collected from three non‐lactating cows fed on a hay and concentrate diet with or without CNSL supplementation. DNA and complementary DNA (cDNA) libraries were generated for investigating rumen microbial communities. MiSeq analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
6
7
0
Order By: Relevance
“…These results agree with the results of the above mentioned feeding (Konda et al, 2019;Maeda et al, 2021;Su et al, 2021) and rumen simulation technique (S. Oh, Shintani, et al, 2017) studies and strongly suggest that alkylphenols selectively inhibit growth once delivered to the rumen environment.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These results agree with the results of the above mentioned feeding (Konda et al, 2019;Maeda et al, 2021;Su et al, 2021) and rumen simulation technique (S. Oh, Shintani, et al, 2017) studies and strongly suggest that alkylphenols selectively inhibit growth once delivered to the rumen environment.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the effects of alkylphenol components of CNSL on cell morphology, in particular anacardic acid, were clearly visualized using microscopic observations. Taken together, these data suggest that the rumen microbial community can be altered to reduce methane emissions and enhance propionate production via selective suppression of hydrogen-and formate-producing bacteria, as reported previously (Kang et al, 2018;Konda et al, 2019;Maeda et al, 2021;Shinkai et al, 2012;Su et al, 2021;Watanabe et al, 2010). Specific genera/ species/strains of methanogenic archaea affected by CNSL were also identified in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A > 50% decrease in methane production potential was achieved in Thai ruminant animals by altering the rumen microbial community structure through selective inhibition of specific microbes mediated by CNSL (Konda et al, 2019). A similar result was observed in Holstein cattle fed CNSL (Su et al, 2021). Konda et al (2019) reported that the surfactant action of alkyl phenols, in particular anacardic acid, is stably maintained in the rumen, although anacardic acid is decarboxylated and becomes less active in the rumen of Japanese Holstein cows (Shinkai, unpublished results).…”
Section: Introductionmentioning
confidence: 59%